The Synthetic Nitrogen Industry in World War I Its Emergence and Expansion - S. Travis, Anthony (History of Chemistry, 2015)
This concise brief describes how the demands of World War I, often referred to as the Chemists' War, led to the rapid emergence of a new key industry based on fixation of atmospheric nitrogen. Then, as now, nitrogen products, including nitric acid, and nitrates, were essential for both fertilizers and in the manufacture of modern explosives. During the first decade of the twentieth century, this stimulated research into and application of novel processes. This book illustrates how from late 1914 the relations and developments in the first modern military-industrial complex enabled the great capital expenditures and technological advances that accelerated massive expansion, particularly of the BASF Haber-Bosch high-pressure process, that determined the direction of the post-war chemical industry. .